Manejo de residuos en el Proyecto Trópika como alternativa sostenible para la construcción en Costa Rica - Vega-Mojica, Daylin Alejandra (Instituto Tecnológico de Costa Rica, 2015)
In Costa Rica the majority of construction waste, is deposited in slag heaps or landfills, which are scarce and even insufficients. When applying the waste hierarchy in a constructive process, is to reduce the amount of waste that contemplate that scenario. The waste management is one of the most critical areas in making a constructive work, therefore, through this work, a methodology applied to waste generated in construction Tropika project was developed to consider sustainable construction. In building the module “Tropika” house waste management guidelines in their planning were established considering storing these on the site and disposal. At the construction site six tanks labeled recyclable waste is placed, these once filled, its contents in bags inside the timber at Sawmill Technological Institute Costa Rican was kept, until you have enough to full a truck and take it even material, however some of these residues were reused on site. The place was left mostly waste for disposal, was the accumulation center MADI, at the Technological. Whether in co-processing, reuse on CTTM or landfill, by type of material. Documentation of types and quantities of waste generated in the construction of the module and some miscellaneous waste generated compared to other constructions, a theoretically and another with a visit to the construction finally of the house, a generation rate was calculated waste estimated that the index waste generation for the module was 6,44 kg/m2. And with that data estimate the producing 21,5 tons of solid waste Tropika housing project as proposed in scale dwelling was planned, there was fed and sets improvement in waste management strategy, in order to reduce them to build Tropika in dwelling buildings. The residues were characterized and classifying this information on type and quantity documented.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2015.
Keywords: Construcción; Madera; Materiales; Reciclaje; Gestión ambiental; Competencia